Renal Amyloidosis: A Narrative Literature Review - Syahpri Putra Wangsa; Novadian Suhaimi; Zulkhair Ali; Suprapti Slamet; Ian Effendi; Kgs M Yusuf Arief Akbar; Deddy Primadona Mulia (HM Publisher, 2023)
Amyloidosis is a disorder in which soluble proteins aggregate and are deposited extracellularly in tissues as insoluble fibrils, causing progressive organ dysfunction. Amyloid fibril formation begins with misfolding of amyloidogenic precursor proteins. The fibrils have a characteristic appearance by electron microscopy and produce double refraction under polarized light when stained with Congo red dye. Classification of amyloidosis is based on the precursor proteins that form amyloid fibrils and the distribution of amyloid deposition both systemically and locally. The main form of systemic amyloidosis; AL amyloid, AA amyloidosis, ATTR amyloid. The kidney is the organ most frequently involved in systemic amyloidosis. Systemic amyloidosis may originate from anomalous proteins, such as immunoglobulin light chains or serum amyloid protein in chronic inflammation or may arise from hereditary disorders. The clinical manifestations of renal amyloidosis vary with the type of amyloid protein and the location and extent of amyloid deposition. Treatment of amyloidosis should be a two-part process; managing symptoms and reducing or stabilizing amyloid protein. Treatment of amyloidosis is focused on reducing the production of amyloidogenic proteins and inhibiting their aggregation.